Peel stress analysis of composite joints for debonding - Notaria Manav Baiju (Nanyang Technological University, 2024)
Adhesive bonding is a prevalent method employed in the fabrication of advanced technical products featuring intricate geometries. This research aims to examine the failure attributes of adhesives with and without Thermoexpancel particles. Glass Fibre Reinforced Polymer (GFRP) and Aluminium Steel Strip (Al) were bonded using 3M™ Scotch Weld™ Epoxy Adhesive DP460 and 3M™ Scotch-Weld™ Epoxy Adhesive DP100, mixed with varying weights of Thermoexpancel particles. The performance of these adhesives was tested under normal room temperature conditions using a customized Floating Roller Peel Test coupled with a Tensile Test machine. This study provides insights into the load-displacement behaviour and failure mechanisms of the adhesives, contributing to the understanding and optimization of debonding techniques for composite materials.